2019
DOI: 10.1111/bph.14558
|View full text |Cite
|
Sign up to set email alerts
|

The combination of metformin and 2‐deoxyglucose significantly inhibits cyst formation in miniature pigs with polycystic kidney disease

Abstract: Background and Purpose The pathogenic mechanism of autosomal dominant polycystic kidney disease (ADPKD) is unclear. Similar to tumour cells, polycystic kidney cells are primarily dependent on aerobic glycolysis for ATP production. Compared with rodents, miniature pigs are more similar to humans. This study is the first time to investigate the effects of the combination of metformin and 2‐deoxyglucose (2DG) in a pig model of chronic progressive ADPKD. Experimental Approach A miniature pig ADPKD model was establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…However, the bioavailability of oral metformin is only ~50% [26,27]. More recently, oral metformin treatment was reported to slow PKD progression in a miniature pig model using a dose of 41∙7 mg/kg/day [52]. However, the estimated human equivalent dose used for this study is 2∙77 g/day, which is higher than the usual dose (2 g/day) used clinically (see supplementary data) [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, the bioavailability of oral metformin is only ~50% [26,27]. More recently, oral metformin treatment was reported to slow PKD progression in a miniature pig model using a dose of 41∙7 mg/kg/day [52]. However, the estimated human equivalent dose used for this study is 2∙77 g/day, which is higher than the usual dose (2 g/day) used clinically (see supplementary data) [53].…”
Section: Discussionmentioning
confidence: 99%
“…The blots were subsequently probed with HRP-conjugated anti-mouse (Cat# A0216) or anti-rabbit IgG (Cat# A0208; Beyotime Biotechnology, Beijing, China) at 1:1000. Immunoreactive bands were visualized by enhanced chemiluminescence, and densitometry was performed using ImageJ software (RRID: SCR_003070, Bio-Rad Laboratories)' [131].…”
Section: Subitem 9b-examplementioning
confidence: 99%
“…Furthermore, liver cysts were reported to be present in all investigated animals. This model was first used in a study by Lian et al published in 2019 [ 193 ], in which the effect of single and combined treatments with 2Deoxy-D-glucose (2DG, an inhibitor of glycolysis reported to reduce cysts growth in mouse PKD models [ 194 , 195 ]) and metformin (an AMP-activated protein kinase inhibitor) on ADPKD progression was investigated. They found that all drug treatments significantly inhibited cyst growth in the ADPKD mini-pig model, the combined therapy being the most effective.…”
Section: In Vivo Research Modelsmentioning
confidence: 99%